PRODUCTION OF BIOGAS FROM ORGANIC WASTE FROM SOYBEAN CLEANING - Bošnjaković, Matko; Gantner, Vesna; Antunović, Sanja; Kralik, Davor (Works of the Faculty of Agriculture and Food Sciences University of Sarajevo, 2026)
Soy is mainly used as a base for the production of food. The first step in the technological processing of soybeans is mechanical cleaning from impurities. Cleaning process creates waste with great energy potential. In 2021 228.000 tons of soybeans were produced in the Croatia, and according to data for 2022 from one of the buyers of soybeans in the Croatia, the average amount of impurities was 6,79%. Taking into account the stated percentage of impurities, we can conclude that in 2021 about 15.481 tons of waste from soybean were generated. By using the mentioned waste as a raw material in the anaerobic digestion process, a significant amount of biogas can be produced, which can be used as fuel for energy production. Laboratory tests have shown that one ton of soybean cleaning waste can produce about 513,81 m3of biogas, of which about 57,2% is CH4. We calculate that the specified amount of waste is sufficient for the production of 19.000 MWh of electrical energy per year. With the average consumption of electrical energy in households in 2021 in Croatia of 2.728 kWh, the total electrical energy produced from soybean waste is sufficient to meet the annual electrical energy needs of 6,980 households.